2008
DOI: 10.1089/vbz.2007.0224
|View full text |Cite
|
Sign up to set email alerts
|

American Trypanosomiasis in Dogs from an Urban and Rural Area of Yucatan, Mexico

Abstract: American trypanosomiasis in dogs is reported from South of the United States to Argentina and Chile. It is transmitted through the contact of dogs with reduviid insects when they feed; reduviid insects are well established in the southern state of Yucatan, Mexico. However, there are no reports available about trypanosomiasis prevalence in dogs of urban and rural areas. A cross-sectional study was performed in 345 stray dogs, 102 from a rural community of Yucatan (Tunkas) and 243 from Merida, capital city of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
42
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 32 publications
9
42
1
1
Order By: Relevance
“…When compared with dogs in Colonia A (the model referent), dogs in Colonia F had significantly lower odds of being seropositive. The county of Colonia F has a lower percentage of Hispanics and is more rural than the counties of the other sampled colonias,64 congruent with a prior study found lower seroprevalence in rural dogs as compared with urban dogs 65…”
Section: Discussionsupporting
confidence: 82%
“…When compared with dogs in Colonia A (the model referent), dogs in Colonia F had significantly lower odds of being seropositive. The county of Colonia F has a lower percentage of Hispanics and is more rural than the counties of the other sampled colonias,64 congruent with a prior study found lower seroprevalence in rural dogs as compared with urban dogs 65…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were obtained using TIA in Amerindians and in patients suffering idiopathic megasyndrome with a history of exposure to T. cruzi (3,15). CS false-negative results in dog samples were also revealed by a dipstick test (6) and PCR (19). Taken together, the evidence shows that TIA detects T. cruzi infections in domestic animal reservoirs that are missed by CS.…”
Section: Discussionsupporting
confidence: 75%
“…These data suggest that stray dogs may be more vulnerable, because they are more exposed to peridomestic transmission; whereas pet dogs that live inside houses are more protected from infection. If we compare the 7.6% of T. cruzi positive dog population in Campeche with that recently reported of 14% in Yucatán ( Jimenez-Coello et al 2008), it represents a little more than half of infection in Campeche, in spite of the fact that the vector is the same in both regions. One possible explanation could be that the infection rate of T. dimidiata in Yucatán can reach up to 46% as reported (Guzman-Tapia et al 2005); whereas for Campeche, the infection rate in T. dimidiata is around 20% (unpublished data).…”
mentioning
confidence: 76%